2018
DOI: 10.1080/15384101.2018.1556060
|View full text |Cite
|
Sign up to set email alerts
|

MiR-221 is involved in depression by regulating Wnt2/CREB/BDNF axis in hippocampal neurons

Abstract: Objective: The aim of this study was to investigate the mechanism of miR-221 in depression. Methods: The molecules expressions were measured by qRT-PCR and western blot. The sucrose preference test (SPT), forced swimming test (FST) and tail suspension test (TST) were used to detect depressive-like symptoms. MTT assay and flow cytometric was used to measure the proliferation and apoptosis of hippocampal neuronal. Results: MiR-221 expression in the cerebrospinal fluid and serum of major depressive disorder patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…CREB is a transcription factor, and its interaction with BDNF has a critical role in the altered neuroplasticity observed in major depression. Consistently, our previous iTRAQ-based proteomics analysis reported a disruption of the CAMKII-CREB-BDNF signaling pathway in gut microbiome remodeling mice 60 , and p-CREB was decreased in the hippocampus of chronic unpredictable mild stress exposed mice 61 . In addition, increased p-CREB is related to treatment response in MDD patients 62 .…”
Section: Discussionsupporting
confidence: 84%
“…CREB is a transcription factor, and its interaction with BDNF has a critical role in the altered neuroplasticity observed in major depression. Consistently, our previous iTRAQ-based proteomics analysis reported a disruption of the CAMKII-CREB-BDNF signaling pathway in gut microbiome remodeling mice 60 , and p-CREB was decreased in the hippocampus of chronic unpredictable mild stress exposed mice 61 . In addition, increased p-CREB is related to treatment response in MDD patients 62 .…”
Section: Discussionsupporting
confidence: 84%
“…Another research showed that MK-801 administration also inhibited the phosphorylation of CREB in the rat hippocampus (33). CREB is the upstream transcription factor of BDNF and inhibited CREB phosphorylation downregulates BDNF expression (34). In the neonatal rat schizophrenia model induced by MK-801 administration, we observed the inhibited phosphorylation of CREB in the hippocampus.…”
Section: Discussionmentioning
confidence: 58%
“…Using a dominant-negative CREB mutant, it has been identified that CREB signaling is essential for the survival and differentiation of newborn neurons [62][63][64]. In addition, CREB phosphorylation is known to increase BDNF expression [65][66][67]. In our study, we detected the activation of CREB phosphorylation and the induction of BDNF expression upon MG132 treatment.…”
Section: Discussionmentioning
confidence: 61%